2013
DOI: 10.2169/internalmedicine.52.8152
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiological Features of <i>Shewanella</i> Bacteremia in Patients with Hepatobiliary Disease

Abstract: Objective Shewanella bacteremia is an uncommon but potentially fatal disease. Although hepatobiliary diseases have been proposed to be risk factors for various Shewanella infections, little is known about the features of Shewanella bacteremia in patients with hepatobiliary diseases. This study aims to characterize the presentation and risk factors of Shewanella bacteremia in patients with hepatobiliary diseases. Methods We retrospectively investigated the clinical features, microbiology and outcomes of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 47 publications
2
69
0
Order By: Relevance
“…The sensitivity findings of our study are in complete agreement with those reported by other investigators [7,15,16]. There are reports of multidrug resistance in Shewanella [10,12,22].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The sensitivity findings of our study are in complete agreement with those reported by other investigators [7,15,16]. There are reports of multidrug resistance in Shewanella [10,12,22].…”
Section: Discussionsupporting
confidence: 93%
“…Available data suggest that Shewanella species are susceptible to aminoglycosides, quinolones, extended-spectrum cephalosporins, ß-lactamase inhibitor combinations and carbapenems [4,7]. However recent epidemiological data showed an increasing frequency of drug resistance especially to piperacillin-tazobactam and imipenem and was attributed to the presence of derepressed ambler class D beta-lactamases in them [6,14,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since S. algae was added to the database of commercial identification systems a decade ago, this species has been easily differentiated from S. putrefaciens. S. algae causes a wide range of infections, including otitis media, cholecystitis, cholangitis, liver abscess, bacteremia, nonhealing ulcer, gastroenteritis, osteomyelitis, cellulitis, pneumonia, peritonitis, and septicemia, similar to V. vulnificus (9)(10)(11)(12)(13)(14). In 2007, S. haliotis was first isolated from the gut microflora of abalone by Kim et al (6).…”
Section: Discussionmentioning
confidence: 99%
“…As the Clinical and Laboratory Standards Institute (CLSI) has not provided the minimal inhibitory concentration (MIC) interpretative standards for Shewanella spp., we applied CLSI-approved standard M100-S22 (9). As only 2 Shewanella spp., S. putrefaciens and S. algae, were registered in the database of the VITEK 2 system, additional identification by using 16S rRNA gene sequence analysis (Macrogen, Seoul, Korea) and MALDI-TOF MS (bioM áerieux Inc.) with the database V2 released in November 2012 were performed.…”
Section: Methodsmentioning
confidence: 99%